Elastin-like polypeptide-alginate composite hydrogel and its preparation method and application

By constructing a composite network hydrogel of elastin-like polypeptides and alginate, the problems of fast degradation speed and insufficient mechanical properties of existing biomaterials are solved, and the biocompatibility and mechanical properties are improved, and it is suitable for a variety of biomedical and cosmetic applications.

CN115819797BActive Publication Date: 2025-04-22SHANGPU BOYUAN (BEIJING) BIOTECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211237015.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-10
Publication Date
2025-04-22
Estimated Expiration
2042-10-10

AI Technical Summary

Technical Problem

Existing biological materials degrade rapidly in vivo and require frequent supplementation. The mechanical properties of single network hydrogels are insufficient, which limits their application in the fields of biomedical and cosmetics.

Method used

Complex network hydrogels are constructed using elastomeric polypeptides and alginates. The temperature sensitivity of elastomeric polypeptides is imparted through chemical modification, and an ionic cross-linking network is formed by chelating metal ions with alginates to form a composite hydrogel.

Benefits of technology

It has achieved improvements in biocompatibility and mechanical properties, with the advantages of injectable, temperature sensitive and high mechanical properties, and is suitable for biomaterial engineering, tissue engineering and cosmetic filling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003883478870000011
    Figure HDA0003883478870000011
  • Figure HDA0003883478870000012
    Figure HDA0003883478870000012
  • Figure HDA0003883478870000013
    Figure HDA0003883478870000013
Patent Text Reader

Abstract

The present invention provides an elastin-like polypeptide-alginate composite hydrogel and its preparation method and application. The preparation method of the elastin-like polypeptide-alginate composite hydrogel comprises: (1) contacting the elastin-like polypeptide with methacrylic anhydride in water to obtain a methacrylic acid-modified elastin-like polypeptide; (2) contacting the methacrylic acid-modified elastin-like polypeptide with alginate in water. Further, the composite hydrogel is subjected to secondary cross-linking and curing with a metal salt solution (the metal cation is divalent or above) to prepare a composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling. The elastin-like polypeptide and alginate used in the hydrogel both have good biocompatibility and stability, and the composite hydrogel prepared at the same time has good temperature sensitivity, injectability and mechanical properties, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material engineering, and in particular relates to an elastin-like polypeptide-alginate composite hydrogel and a preparation method and application thereof. Background Art

[0002] Hydrogel is a material constructed of a hydrophilic polymer network with water as the dispersion medium. Because it is similar to many characteristics of the extracellular matrix, it has received widespread attention in the fields of biomedicine and beauty, especially in the field of cosmetic filling. From the perspective of material sources, the sources of biomaterials on the market are mainly collagen and hyaluronic acid, which limits the user's choice. In addition, the above biomaterials degrade rapidly in the body and need to be continuously supplemented with new filling materials. In addition, the biomaterials currently used for filling are mainly traditional single-network hydrogels in terms of cross-linking mechanism. Due to their single cross-linking mechanism, they exhibit weak mechanical properties, which seriously hinders the application of hydrogels in the fields of biomedicine and beauty. Therefore, composite network hydrogels composed of two different cross-linking networks are increasingly attracting people's attention. Summary of the invention

[0003] The purpose of the present invention is to provide a novel elastin-like polypeptide-alginate composite hydrogel and a preparation method and application thereof.

[0004] The concept of the present invention is as follows: In order to meet the diverse needs of consumers, the present invention provides a strategy for constructing a composite network hydrogel using two natural polymers, elastin-like polypeptides and alginate. First, the temperature-sensitive property of the elastin-like polypeptide is given by chemical modification of the hydrophobic group, so that it behaves as a gel when close to the human body temperature and as a solution at low temperatures, and is used to construct the first layer of hydrophobic cross-linked network, which has the characteristics of being injectable and temperature-sensitive. Secondly, the pre-mixed alginate can chelate with metal ions to form an ion cross-linked network, and the first layer system is immersed in a metal ion solution to induce secondary cross-linking, and finally a composite network hydrogel is formed. The hydrogel has excellent biocompatibility and mechanical properties, and has good application prospects as a tissue engineering material.

[0005] In order to achieve the purpose of the present invention, in a first aspect, the present invention provides a method for preparing an elastin-like polypeptide-alginate composite hydrogel, comprising the following steps:

[0006] (1) contacting an elastin-like polypeptide with methacrylic anhydride in water to obtain an elastin-like polypeptide modified with methacrylic acid (i.e., a polypeptide derivative); the polypeptide derivative is temperature sensitive;

[0007] (2) The methacrylic acid-modified elastin-like polypeptide is fully contacted with alginate in water (the mixed system has injectability and temperature sensitivity) to obtain an elastin-like polypeptide-alginate composite hydrogel.

[0008] In the present invention, the amino acid sequence of the elastin-like polypeptide is [(VPGVG)2VPGKG(VPGVG)2] 25 (SEQ ID NO: 1).

[0009] In the aforementioned method, step (1) specifically comprises: dissolving the elastin-like polypeptide in water, adjusting the solution pH to 7.0-8.0 (using 0.1M NaOH), adding methacrylic anhydride to react (methacrylic anhydride reacts with the free amino group on the lysine in the amino acid sequence of the elastin-like polypeptide after hydrolysis) to obtain a methacrylic acid-modified elastin-like polypeptide, dialyzing in deionized water after the reaction, and freeze-drying to obtain a methacrylic acid-modified elastin-like polypeptide.

[0010] Furthermore, in step (1), the molar ratio of the elastin-like polypeptide to methacrylic anhydride is (0.5-10):(1-100).

[0011] Furthermore, in step (1), the reaction temperature is 4-15° C., and the reaction time is 4-48 h.

[0012] The alginate is preferably sodium alginate, and the viscosity of the sodium alginate is 20-800 MPa·s.

[0013] Furthermore, in step (2), the molar ratio of the methacrylic acid-modified elastin-like polypeptide to alginate is (1-10):(1-5).

[0014] Step (2) is carried out at room temperature.

[0015] In a second aspect, the present invention provides an elastin-like polypeptide-alginate composite hydrogel prepared according to the method. The composite hydrogel is in a gel state when the temperature is increased, and in a solution state when the temperature is decreased.

[0016] In a third aspect, the present invention provides a composite network hydrogel, which is formed by mixing the elastin-like polypeptide-alginate composite hydrogel with a metal salt solution.

[0017] Wherein, the metal cations in the metal salt solution are divalent or higher, such as calcium ions, aluminum ions, etc.

[0018] Furthermore, the concentration of metal cations in the metal salt solution is 0.1 to 5 mol / L.

[0019] In a fourth aspect, the present invention provides any of the following applications of the elastin-like polypeptide-alginate composite hydrogel or the composite network hydrogel:

[0020] 1) Used in biomaterials engineering;

[0021] 2) Used in tissue engineering;

[0022] 3) Used as cosmetic filling material.

[0023] By means of the above technical solution, the present invention has at least the following advantages and beneficial effects:

[0024] (I) From the perspective of material sources, the hydrogel is composed of natural polymer materials such as elastin-like polypeptides and alginate. Elastin is an important extracellular matrix protein, and its main function is to give the tissue or organ in which it is located elasticity and reversible deformation ability. Therefore, there are a large number of elastin in organs that are often deformed by force, such as skin, arteries and lungs. Elastin-like polypeptides are polypeptides with elastin characteristics designed and synthesized based on the amino acid sequence of natural elastin. The hydrogel prepared from it has good mechanical properties and biocompatibility, and has therefore received widespread attention in the biomedical field. Alginate is a byproduct of extracting iodine and mannitol from kelp or sargassum of brown algae. It is a natural polysaccharide with good biocompatibility and stability, and has been widely used in the food industry and the medical field.

[0025] (ii) Compared with traditional hydrogels, it has the following characteristics: First, it has reversible temperature-sensitive properties, can solidify when close to human body temperature, and maintain a fluid state when below human body temperature, so that it has the advantages of in-situ injection and solidification; second, compared with single-network hydrogels, it has stronger mechanical properties, because it is a composite hydrogel formed by a layer of hydrophobic cross-linked network and an ionic cross-linked network, the first layer of network ensures the structural integrity during the force-bearing process, and the second layer of network can provide stress dissipation by breaking, and the two layers work together to make the hydrogel show significantly enhanced mechanical properties; finally, compared with traditional double-network hydrogels that are prone to fatigue during repeated force-bearing, the cross-linked network provided by the present invention has a cross-linking mechanism for dissipating external forces, and the two cross-linked networks are interspersed with each other, eventually forming a natural high-elastic composite network hydrogel. Finally, the entire gelation process is gentle and easy to operate. The present invention has many advantages in terms of injectability, biocompatibility and mechanical properties, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The figure is a hydrogen nuclear magnetic spectrum result of the methacrylic acid modified elastin-like polypeptide prepared in a preferred embodiment of the present invention.

[0027] Figure 2This is a graph showing the injectability results of the composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling prepared in a preferred embodiment of the present invention.

[0028] Figure 3 This is a graph showing the temperature sensitivity of the elastin-like polypeptide-alginate composite hydrogel for cosmetic filling prepared in a preferred embodiment of the present invention.

[0029] Figure 4 This is a digital photo of the composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling prepared in a preferred embodiment of the present invention after secondary curing.

[0030] Figure 5 This is a digital photo of the composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling prepared in a preferred embodiment of the present invention lifting a heavy object after secondary curing.

[0031] Figure 6 This is a comparison chart of the maximum breaking strengths of the methacrylic acid modified elastin-like polypeptide single network hydrogel, alginate single network hydrogel and elastin-like polypeptide-alginate composite hydrogel prepared in the preferred embodiment of the present invention.

[0032] Figure 7 This is a graph showing the stress change results of the methacrylic acid modified elastin-like polypeptide-alginate composite hydrogel prepared in a preferred embodiment of the present invention after repeated stress-recovery.

[0033] Figure 8 This is a graph showing the live-death results of fibroblasts cultured on the methacrylic acid-modified elastin-like polypeptide-alginate composite hydrogel prepared in a preferred embodiment of the present invention.

[0034] Fig. 9 The graphs are the degradation results of the methacrylic acid-modified elastin-like polypeptide-alginate composite hydrogel prepared in the preferred embodiment of the present invention in mice and the immunohistochemistry results. DETAILED DESCRIPTION

[0035] The invention provides a composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling and a preparation method thereof.

[0036] The method for preparing the composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling comprises the following steps:

[0037] (1) taking an elastin-like polypeptide and a modifier, reacting to obtain an elastin-like polypeptide derivative, wherein the elastin-like derivative is an elastin-like polypeptide modified with methacrylic acid;

[0038] (2) fully dissolving the elastin-like polypeptide derivative in an aqueous solution, and then mixing it with alginate, wherein the mixed system exhibits a gel state when the temperature is increased and exhibits a solution state when the temperature is decreased;

[0039] (3) The composite hydrogel is then subjected to secondary cross-linking and curing with a metal salt solution, wherein the metal cations in the metal salt solution are divalent or higher, to prepare an elastin-like polypeptide-alginate composite hydrogel that can be used for cosmetic filling.

[0040] In the above step (1), the elastin-like polypeptide is fully dissolved in water, methacrylic anhydride is added dropwise to react, and the pH is maintained between 7 and 8. After the reaction is completed, it is dialyzed in deionized water and freeze-dried to obtain a methacrylic acid-modified elastin-like polypeptide.

[0041] In the above method, the amino acid sequence of the elastin-like polypeptide is [(VPGVG)2VPGKG(VPGVG)2] 25 , its concentration is 0.5% ~ 10%.

[0042] In the above method, the molar ratio of the elastin-like polypeptide to methacrylic anhydride is (0.5-10): (1-100).

[0043] In the above method, the reaction temperature is 4 to 15°C and the reaction time is 4 to 48 hours.

[0044] In the above step (2), the elastin-like polypeptide derivative is fully dissolved in an aqueous solution and then mixed with alginate. When the temperature is increased, the composite system exhibits a gel state, and when the temperature is decreased, it exhibits a solution state. The network has the characteristics of being injectable and temperature-sensitive.

[0045] The molar ratio of the methacrylic acid-modified elastin-like polypeptide to alginate is (1-10):(1-5).

[0046] In the above method, the viscosity of sodium alginate is 20-800 MPa·s.

[0047] In the above step (3), the composite hydrogel and the metal salt solution are subjected to secondary cross-linking and curing, and the metal cations in the metal salt solution are divalent or above, so as to prepare a composite hydrogel of elastin-like polypeptide-alginate that can be used for cosmetic filling.

[0048] In the above method, the concentration of metal cations in the metal salt solution used is 0.1 to 5 mol / L.

[0049] In the above method, the soaking time in step (3) is 2 to 200 minutes.

[0050] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art, and the raw materials used are all commercially available products. Example 1 Preparation of elastin-like polypeptide-alginate composite hydrogel for cosmetic filling

[0051] (1) An elastin-like polypeptide (SEQ ID NO: 1) and a modifier are reacted to obtain an elastin-like polypeptide derivative, wherein the elastin-like polypeptide derivative is an elastin-like polypeptide modified with methacrylic acid. Specifically, the elastin-like polypeptide is:

[0052] 1g of elastin-like polypeptide was fully dissolved in 100mL of deionized water, and the pH of the solution was adjusted to 7.5-8.0 with 0.1M NaOH, followed by adding 3.85g of methacrylic anhydride and stirring at 5°C for 24h. After the reaction, it was dialyzed in deionized water for 3 days and freeze-dried to obtain a white flocculent methacrylic acid-modified elastin-like polypeptide. The results of the H-NMR spectrum of the prepared methacrylic acid-modified elastin-like polypeptide are shown in Figure 1 .

[0053] (2) The elastin-like polypeptide derivative is fully dissolved in an aqueous solution, and then mixed with alginate, wherein the mixed system is in a gel state when the temperature is increased and in a solution state when the temperature is decreased. The details are as follows:

[0054] 500 mg of methacrylic acid-modified elastin-like polypeptide was dissolved in 5 mL of deionized water and stirred thoroughly until completely dissolved. Then, 500 mg of sodium alginate was added and stirred vigorously until completely dissolved. The mixed system had injectability and temperature sensitivity.

[0055] (3) The methacrylic acid modified elastin-like polypeptide single network hydrogel is subjected to secondary cross-linking and curing with a metal salt solution, wherein the metal cations in the metal salt solution are divalent or higher, to prepare an elastin-like polypeptide-alginate composite hydrogel that can be used for cosmetic filling. The details are as follows:

[0056] The mixed system hydrogel is immersed in a 0.5 M calcium ion solution for secondary cross-linking and taken out after 10 minutes to obtain a composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling.

[0057] Example 2 Preparation of elastin-like polypeptide-alginate composite hydrogel for cosmetic filling

[0058] (1) An elastin-like polypeptide and a modifier are reacted to obtain an elastin-like polypeptide derivative, wherein the elastin-like polypeptide derivative is an elastin-like polypeptide modified with methacrylic acid. The details are as follows:

[0059] 1 g of elastin-like polypeptide was fully dissolved in 200 mL of deionized water, and the pH of the solution was adjusted to 7.5-8.0 with 0.1 M NaOH, followed by adding 2 g of methacrylic anhydride and stirring at 10°C for 24 h. After the reaction, the solution was dialyzed in deionized water for 3 days and freeze-dried to obtain a white flocculent methacrylic acid-modified elastin-like polypeptide.

[0060] (2) The elastin-like polypeptide derivative is fully dissolved in an aqueous solution, and then mixed with alginate, wherein the mixed system is in a gel state when the temperature is increased and in a solution state when the temperature is decreased. The details are as follows:

[0061] Take 200 mg of methacrylic acid modified elastin polypeptide and dissolve it in 3 mL of deionized water, stir it thoroughly until it is completely dissolved, then add 500 mg of sodium alginate and stir it vigorously until it is completely dissolved. The mixed system has injectable and temperature-sensitive properties. The details are as follows:

[0062] (3) The methacrylic acid modified elastin-like polypeptide single network hydrogel is subjected to secondary cross-linking and curing with a metal salt solution, wherein the metal cations in the metal salt solution are divalent or above, to prepare an elastin-like polypeptide-alginate composite hydrogel that can be used for cosmetic filling.

[0063] The methacrylic acid modified elastin-like polypeptide single network hydrogel is immersed in a 0.5 M aluminum ion solution for secondary cross-linking and taken out after 10 minutes to obtain an elastin-like polypeptide-alginate composite hydrogel for cosmetic filling.

[0064] The experimental results are similar to those of Example 1.

[0065] Example 3 Performance of the composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling

[0066] 1. The injectability of the composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling prepared by the present invention is shown in Figure 2 .

[0067] 2. Temperature sensitivity test of elastin-like polypeptide-alginate composite hydrogel for cosmetic filling

[0068] Under room temperature, 1 g of methacrylic acid-modified elastin-like polypeptide (prepared in Example 1) was dissolved in 10 mL of deionized water and stirred thoroughly until completely dissolved. Then, 1 g of sodium alginate was added and stirred vigorously until completely dissolved to obtain a milky white uniform liquid. The mixed system was heated and cooled to observe the change in the fluidity of the mixed system. The experimental results are shown in Figure 3 ,from Figure 3It can be seen that as the temperature decreases, the mixed system changes from a solid state to a liquid mixture with a certain fluidity, and when the temperature is increased, the liquid can be transformed into a solid state again.

[0069] 3. A digital photo of the composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling prepared by the present invention after secondary curing is shown in Figure 4 .

[0070] 4. Mechanical properties of elastin-like polypeptide-alginate composite hydrogel for cosmetic filling

[0071] The mechanical properties test was carried out on an Instron E3000 mechanical tensile testing machine from the United States. Both ends of the sample were fixed on the clamps of the tensile testing machine and the test was carried out at a tensile rate of 2 mm / min until the sample broke. The experiment was terminated and the stress-strain curve of the sample was finally obtained.

[0072] Digital photos of the composite hydrogel of elastin-like polypeptide-alginate for cosmetic filling (prepared in Example 1) lifting a heavy object after secondary curing are shown in Figure 5 .from Figure 5 It can be seen that the composite hydrogel with a length, width and height of 33.33 mm, 18.71 mm and 2.04 mm respectively can lift a weight of 200 g without breaking.

[0073] 5. Investigation of the maximum breaking strength of methacrylic acid-modified elastin-like polypeptide single network hydrogel, alginate single network hydrogel and elastin-like polypeptide-alginate composite hydrogel

[0074] Mechanical properties testing was performed on an Instron E3000 mechanical tensile machine in the United States at a tensile rate of 2 mm / min until the sample broke. The maximum breaking stress can be obtained from the stress-strain curve, which is the stress shown at the breaking point where the stress suddenly drops.

[0075] The maximum breaking strength comparison of methacrylic acid modified elastin-like polypeptide single network hydrogel, alginate single network hydrogel and elastin-like polypeptide-alginate composite hydrogel (prepared in Example 1) is shown in Figure 6 .from Figure 6 It can be seen that the maximum fracture stress of the elastin-like polypeptide-alginate composite hydrogel reached 560KPa, which is significantly higher than that of the two single network hydrogels, showing a significant improvement in mechanical properties.

[0076] 6. Investigation of stress changes of methacrylic acid-modified elastin-like polypeptide-alginate composite hydrogels subjected to repeated stress-recovery

[0077] Fix the sample on the clamp of the tensile testing machine, then set up a cyclic program to repeatedly stretch and recover the sample at a uniform speed, and count the changes in stress values ​​at the same strain.

[0078] The stress change results of methacrylic acid modified elastin polypeptide-alginate composite hydrogel (prepared in Example 1) after repeated force-recovery are shown in Figure 7 .from Figure 7 It can be seen that as the composite hydrogel was repeatedly stretched and recovered, the sample did not break and showed a basically consistent tensile stress value of about 500 KPa.

[0079] 7. Cultivation of fibroblasts in methacrylic acid-modified elastin-like polypeptide-alginate composite hydrogel

[0080] Fibroblasts (mouse fibroblasts L929) were cultured in a system of RPMI 1640 basal medium + 10% fetal bovine serum (FBS) + 1% penicillin / streptomycin, with a specific ratio of RPMI 1640 basal medium, fetal bovine serum and penicillin / streptomycin of 89:10:1. The composite hydrogel was soaked in the medium overnight, and then the fibroblasts were planted on the surface of the hydrogel and cultured for 1, 3, 7, and 14 days, respectively, and tested using a live-death test kit to obtain the cell survival rate.

[0081] The results of the live and dead of fibroblasts cultured in the methacrylic acid modified elastin polypeptide-alginate composite hydrogel (prepared in Example 1) are shown in Figure 8 .from Figure 8 It can be seen that although the cell survival rate decreased with the extension of culture time, it remained above 84%, which shows the good cell compatibility of the composite hydrogel.

[0082] 8. In vivo test of methacrylic acid modified elastin-like polypeptide-alginate composite hydrogel

[0083] Before implantation, the composite hydrogel (prepared in Example 1) was first disinfected with 75% alcohol, then rinsed and soaked with sterile water. Then, adult mice (6-8 weeks, weighing 20-30 g) (n=4) were taken, a 1 cm wound was cut on the back, and the composite hydrogel was placed in the wound, which was then sutured. The mice were sampled 7, 28, and 70 days after implantation, and the weight of the remaining composite hydrogel was weighed. At the same time, immunofluorescence analysis was performed on the composite hydrogel and the tissue wrapped around it.

[0084] The degradation results of methacrylic acid modified elastin-like polypeptide-alginate composite hydrogel in mice and the immunohistochemical results are shown in Fig. 9 .from Fig. 9It can be seen that the composite hydrogel maintained at least 90% of its original weight after 7, 28, and 70 days after implantation, showing good in vivo stability. Immunofluorescence results also showed that the composite hydrogel had a weak inflammatory response after implantation in vivo, showing good biocompatibility.

[0085] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A composite network hydrogel, characterized in that: It is composed of a mixture of elastin-like polypeptide-alginate composite hydrogel and a metal salt solution; Wherein, the metal cations in the metal salt solution are divalent or higher; The preparation method of the elastin-like polypeptide-alginate composite hydrogel comprises the following steps: (1) contacting an elastin-like polypeptide with methacrylic anhydride in water to obtain an elastin-like polypeptide modified with methacrylic acid; (2) contacting the methacrylic acid-modified elastin-like polypeptide with alginate in water to obtain an elastin-like polypeptide-alginate composite hydrogel; Wherein, the amino acid sequence of the elastin-like polypeptide is shown in SEQ ID NO:

1.

2. The composite network hydrogel according to claim 1, characterized in that Step (1) is specifically as follows: dissolving the elastin-like polypeptide in water, adjusting the solution pH to 7.0-8.0, adding methacrylic anhydride to react, dialyzing in deionized water after the reaction, and freeze-drying to obtain a methacrylic acid-modified elastin-like polypeptide.

3. The composite network hydrogel according to claim 2, characterized in that: The molar ratio of the elastin-like polypeptide to methacrylic anhydride in step (1) is (0.5-10): (1-100).

4. The composite network hydrogel according to claim 2, characterized in that: The reaction temperature in step (1) is 4-15°C and the reaction time is 4-48h.

5. The composite network hydrogel according to claim 1, characterized in that: The alginate is sodium alginate, and the viscosity of the sodium alginate is 20-800 MPa·s.

6. The composite network hydrogel according to claim 5, characterized in that The molar ratio of the methacrylic acid-modified elastin-like polypeptide to alginate in step (2) is (1-10): (1-5).

7. The composite network hydrogel according to claim 1, characterized in that The concentration of metal cations in the metal salt solution is 0.1-5 mol / L.

8. Any of the following uses of the composite network hydrogel according to any one of claims 1 to 7: 1) Used for preparing bioengineering materials; 2) Used to prepare cosmetic filling materials.

Citation Information

Patent Citations

  • Bio-macromolecular hydrogel and preparation method thereof

    CN102688525A